Optimizing the Performance of Satreskrim in Handling the Crime of Theft with Ballast to Improve Crime Clearance in the Jurisdiction of Pekalongan Police Station (Advances in Police Science Research Journal, 2024)
Performance is one of the references of a person's results in carrying out tasks in an organization. This reference can see whether the work done according to the criteria or not. The Criminal Investigation Unit as a repressive function has handled crime cases, especially in the crime of theft by ballast. But the reality is that the settlement of theft cases with ballast has decreased. Therefore, this study wants to explore how efforts in optimize the performance of satreksrim in handling criminal acts of theft with ballast to increase crime clearance in the jurisdiction of Pekalongan Police Station. This research uses a qualitative approach with the type of field study research with the research location at Pekalongan Police Station. This research also uses the analysis knife of organizational management theory and organizational resources and uses concepts related to the focus of the problem formulated. Based on the results of the study, it can be concluded that optimize the performance of the Pekalongan Police Station in handling criminal acts of theft with ballast to increase crime clearance in the jurisdiction of Pekalongan Police Station, have not been maximally caused by internal factors, namely human resources, infrastructure, budget, and operational standards procedures and external factors that include the community and geographical location of Pekalongan Regency. For this reason, it is necessary to problem solving of optimize the performance of satreskrim Pekalongan Police in handling curated criminal acts.
Keywords: Kata Kunci: Kinerja, Tindak pidana curat, Satreskrim Polres Pekalongan